A pre-sodiumized positive electrode sheet and its application as well as a sodium ion battery and its preparation method
By adopting a double-layer structure of high voltage and high capacity sodium ion positive electrode slurry in sodium ion batteries, the problem of low efficiency of the first circle of sodium ion batteries is solved, the energy density and cycle life are improved, and the stability of the electrode sheet is enhanced and low temperature performance, suitable for large-scale manufacturing.
Patent Information
- Application Number
- CN202210380224.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-12
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2042-04-12
AI Technical Summary
The problems of low efficiency, reduced energy density and poor circulation stability of the first circle of existing sodium ion batteries are mainly due to the proportion and volume of active substances in the positive electrode pre-sodiumization technology, resulting in excessive specific surface area of the electrode sheet and interface. Increased side reactions, electrolyte decomposition and electrical performance deterioration.
Using a double-layer structure of high-voltage sodium ion positive electrode slurry and high-capacity sodium ion positive electrode slurry, synthesized by vacuum stirring, it contains high-voltage layered oxide positive electrode material, conductive polymer and dispersant, combined with fibrous polymer conduction Polymers, encapsulating small particle size sodium-rich materials, improve electron conductivity and electrochemical kinetics, and reduce polarization and oxidation potential.
It improves the first-time Coulomb efficiency, energy density, cycle life and low-temperature performance of sodium ion batteries, enhances the reliability and interface stability of the pole sheet, reduces the difficulty of industrialization and production efficiency, and is suitable for large-scale manufacturing.
Smart Images

Figure CN114649504B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a pre-sodiumized positive electrode sheet and application thereof, as well as a sodium ion battery and a preparation method thereof. Background Art
[0002] The performance advantages of lithium-ion batteries have made them widely used in the 3C field, energy storage field and electric vehicle field. However, the uneven distribution of lithium resources, resource shortage, high price and heavy reliance on imports have become increasingly prominent. Therefore, it is particularly important to develop new energy storage devices that can replace or supplement them. Sodium-ion batteries have gained widespread attention and research due to their rich resources, low cost and environmental friendliness. In addition, sodium and lithium belong to the same main group and have similar electrochemical properties. The formula system, process route, production and manufacturing of sodium-ion batteries and lithium-ion batteries are highly compatible with each other, making the rapid industrialization of sodium-ion batteries possible. However, the hard carbon negative electrode used in sodium-ion batteries generally has the problem of low first-cycle coulomb efficiency, which causes problems such as reduced energy density and poor cycle stability of sodium-ion batteries. Therefore, it is particularly important to improve the first-cycle coulomb efficiency of sodium-ion batteries.
[0003] In view of the industry's experience in lithium-ion batteries, the method to improve the first coulomb efficiency is pre-lithium or pre-sodium. The pre-sodiumization of the electrode material can offset the irreversible sodium loss. The conventional pre-sodiumization methods are mainly positive electrode sodium replenishment technology and negative electrode sodium replenishment technology. The positive electrode sodium replenishment technology has good process compatibility, safety and simplicity and convenience, making it possible to implement it in industrialization. Most of the existing positive electrode pre-sodiumization technologies directly add positive electrode sodium compensation materials (or sodium-rich materials) to the positive electrode slurry for use. First, the positive electrode sodium compensation material (hereinafter referred to as CRNa) will occupy a certain proportion and volume of active materials, which will reduce the capacity of the sodium ion battery. Secondly, the residual volume of CRNa after the first sodium removal will leave a large number of gaps, resulting in an excessively large specific surface area of the pole piece, worsening the interface side reaction. At the same time, CRNa will leave a large number of gaps after the reaction, or reduce the adhesion strength of the positive electrode active material, conductive agent & binder, causing the pole piece to fall off or powder. The higher oxidation potential of CRNa will destroy the structure of the active material, cause the electrolyte to decompose, and cause irreversible electrical performance degradation. At the same time, the lower electron transmission and electrochemical kinetics of CRNa will increase polarization, improve reaction potential and time, increase the difficulty of industrialization and production efficiency, and make it more difficult to build a high-performance sodium-ion battery system. Therefore, in the existing technology, the positive electrode plate structure composed of positive electrode sodium compensation materials, as well as the reliability and interface stability of the plate, have great problems, which is a technical bottleneck that needs to be solved urgently in the positive electrode pre-sodiumization technology. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects in the prior art and provide a pre-sodiumized positive electrode plate and its application as well as a sodium ion battery and its preparation method.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a pre-sodiumized positive electrode sheet, which comprises, from top to bottom, a high-voltage sodium ion positive electrode slurry, a high-capacity sodium ion positive electrode slurry and a current collector;
[0007] The thickness of the high-voltage sodium ion positive electrode slurry is 10-15% of the sum of the thickness of the high-voltage sodium ion positive electrode slurry and the high-capacity sodium ion positive electrode slurry.
[0008] Preferably, the high voltage sodium ion positive electrode slurry comprises the following raw materials: a high voltage layered oxide positive electrode material, a positive electrode sodium compensation material, a conductive polymer, a dispersant and a solvent;
[0009] The high voltage layered oxide positive electrode material is P2-Na 2 / 3 [Cu 1 / 3 Mn 2 / 3 ]O2, the positive electrode sodium compensation material comprises Na2C2O4 or Na2MnO3, the conductive polymer is polypyrrole nanofiber, the dispersant comprises sulfonate, sulfate ester salt, carboxylate or oleate; the solvent is N-methylpyrrolidone;
[0010] The mass ratio of the high voltage layered oxide positive electrode material, the positive electrode sodium compensation material, the conductive polymer and the dispersant is 95-97:1.5-2.5:1-2:0.1-1.
[0011] Preferably, the solid content of the high voltage sodium ion positive electrode slurry is 65-75%.
[0012] Preferably, the method for preparing the high-voltage sodium ion positive electrode slurry comprises the following steps: mixing various raw materials to obtain the high-voltage sodium ion positive electrode slurry;
[0013] The mixing is vacuum stirring, the rotation speed of the vacuum stirring is 1500 to 3000 rpm, the time is 4 to 6 hours, and the vacuum degree is -0.05 to -0.08 MPa.
[0014] Preferably, the high-capacity sodium ion positive electrode slurry comprises the following raw materials: a high-capacity layered oxide positive electrode material, a binder, a conductive agent, carbon nanotubes and a solvent;
[0015] The high capacity layered oxide positive electrode material is O3-Na[Cu 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3]O2, the binder is polyvinylidene fluoride, the conductive agent is super-p, and the solvent is N-methylpyrrolidone;
[0016] The mass ratio of the high-capacity layered oxide positive electrode material, the binder, the conductive agent and the carbon nanotube is 94-96:2-3:1.5-2.5:0.1-1.
[0017] Preferably, the solid content of the high-capacity sodium ion positive electrode slurry is 55-65%.
[0018] Preferably, the method for preparing the high-capacity sodium ion positive electrode slurry comprises the following steps: mixing various raw materials to obtain the high-capacity sodium ion positive electrode slurry;
[0019] The mixing is vacuum stirring, the rotation speed of the vacuum stirring is 1500 to 3000 rpm, the time is 4 to 6 hours, and the vacuum degree is -0.05 to -0.08 MPa.
[0020] The present invention also provides the use of the pre-sodiumized positive electrode plate in a sodium ion battery.
[0021] The present invention provides a sodium ion battery, which comprises the pre-sodiumized positive electrode sheet and the hard carbon negative electrode sheet.
[0022] The present invention also provides a method for preparing the sodium ion battery, comprising the following steps: combining a pre-sodiumized positive electrode sheet and a hard carbon negative electrode sheet, and sequentially performing rolling, slitting, sheeting, winding, assembling, baking, liquid injection, formation, aging, and capacity division to obtain the sodium ion battery;
[0023] The step of charging, discharging, and discharging are performed sequentially in the first step, the second step, the third step, and the fourth step.
[0024] The current of the first step charging is 0.15-0.25C, and the target voltage is 3.7-3.9V;
[0025] The current of the second step charging is 0.35-0.45C, and the target voltage is 3.95-4.05V;
[0026] The current of the third step charging is 0.15-0.25C, and the target voltage is 4.3-4.4V;
[0027] The current of the fourth step discharge is 0.15-0.25C, and the target voltage is 3.7-3.9V.
[0028] The invention provides a pre-sodiumized positive electrode pole piece. The high-capacity sodium ion positive electrode slurry can realize the high energy density of the sodium ion battery, and can also lay a foundation for the charging and discharging use of the sodium ion battery throughout its life cycle, and maintain the reliability and integrity of the pole piece. The organic fusion of the high-voltage sodium ion positive electrode material, the fiber high molecular conductive polymer and the sodium-rich material in the high-voltage sodium ion positive electrode slurry can ensure the compatibility with the high-capacity sodium ion positive electrode slurry, so that the two layers of positive electrodes are seamlessly combined. At the same time, the fibrous high molecular conductive polymer can wrap the small-particle sodium-rich material or embed the small-particle sodium-rich material therein, increase the contact sites between the sodium-rich material and the conductive polymer & high-voltage sodium ion positive electrode material, improve the electronic conductivity, improve the electrochemical kinetics, reduce the polarization, reduce the oxidation potential, and avoid the decomposition of the sodium-rich material to increase more pore structures. The high-voltage sodium ion positive electrode slurry can reduce the material structure damage and side reactions at high potential, so that the positive electrode sodium supplement has good voltage matching, interface stability, pole piece structure reliability, high kinetic characteristics, high efficiency and convenience.
[0029] The present invention also provides a sodium ion battery, comprising the pre-sodiumized positive electrode plate and negative electrode material of the present invention. The effective use of the pre-sodiumized positive electrode plate in the present invention reduces the irreversible sodium loss of the hard carbon negative electrode, improves the kinetic performance of the sodium ion battery, and reduces polarization; it can improve the comprehensive electrochemical performance of the sodium ion battery, and create conditions for the development of high-performance sodium ion batteries with high energy density, long cycle life, ultra-low temperature performance, and high rate performance. The technical solution of the present invention is simple to implement, has strong process compatibility, is easy to industrialize, and is suitable for large-scale manufacturing. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a schematic diagram of the structure of the pre-sodiumized positive electrode sheet in Example 1;
[0031] Among them, 1 is a high voltage sodium ion positive electrode slurry, 2 is a high capacity sodium ion positive electrode slurry, 3 is a current collector, and 4 is a fibrous high molecular conductive polymer;
[0032] Figure 2 The first coulombic efficiency-box plot of the sodium ion battery in Example 1 and the comparative example;
[0033] Figure 3 The cycle performance diagram of the sodium ion battery in Example 1 and the comparative example;
[0034] Figure 4 The charge and discharge capacity retention rate diagram of the sodium ion battery at -40°C in Example 1 and Comparative Example;
[0035] Figure 5 The DCR test diagram of the sodium ion battery in Example 1 and the comparative example;
[0036] Figure 6 This is a test diagram of the rate discharge capability of the sodium ion battery of Example 1. DETAILED DESCRIPTION
[0037] The present invention provides a pre-sodiumized positive electrode sheet, which comprises, from top to bottom, a high-voltage sodium ion positive electrode slurry, a high-capacity sodium ion positive electrode slurry and a current collector;
[0038] The thickness of the high-voltage sodium ion positive electrode slurry is 10-15% of the sum of the thickness of the high-voltage sodium ion positive electrode slurry and the high-capacity sodium ion positive electrode slurry.
[0039] In the present invention, the thickness of the high voltage sodium ion positive electrode slurry is 10-15% of the sum of the thickness of the high voltage sodium ion positive electrode slurry and the high capacity sodium ion positive electrode slurry, preferably 11-14%, more preferably 12-13%.
[0040] In the present invention, the high voltage sodium ion positive electrode slurry preferably comprises the following raw materials: a high voltage layered oxide positive electrode material, a positive electrode sodium compensation material, a conductive polymer, a dispersant and a solvent.
[0041] In the present invention, the high voltage layered oxide positive electrode material is preferably P2-Na 2 / 3 [Cu 1 / 3 Mn 2 / 3 ]O2, the positive electrode sodium compensation material preferably comprises Na2C2O4 or Na2MnO3, the conductive polymer is preferably polypyrrole nanofiber, the dispersant preferably comprises sulfonate, sulfate ester, carboxylate or oleate; the solvent is preferably N-methylpyrrolidone.
[0042] In the present invention, the sulfonate is preferably sodium coconut oil isethionate, sodium olefin sulfonate or sodium hydroxy sulfonate.
[0043] In the present invention, the sulfate ester salt is preferably sodium lauryl sulfate or sodium fatty alcohol ether sulfate.
[0044] In the present invention, the carboxylate is preferably sodium carboxylate or potassium carboxylate.
[0045] In the present invention, the oleate is preferably sodium oleate or potassium oleate.
[0046] In the present invention, the mass ratio of the high voltage layered oxide positive electrode material, the positive electrode sodium compensation material, the conductive polymer and the dispersant is preferably 95-97: 1.5-2.5: 1-2: 0.1-1, further preferably 95.4-96.6: 1.6-2.4: 1.2-1.8: 0.2-0.8, and more preferably 95.8-96.2: 1.8-2.2: 1.4-1.6: 0.4-0.6.
[0047] In the present invention, the solid content of the high voltage sodium ion positive electrode slurry is preferably 65-75%, more preferably 66-74%, and even more preferably 68-72%.
[0048] In the present invention, the method for preparing the high-voltage sodium ion positive electrode slurry preferably comprises the following steps: mixing various raw materials to obtain the high-voltage sodium ion positive electrode slurry;
[0049] The mixing is preferably vacuum stirring, and the rotation speed of the vacuum stirring is preferably 1500-3000 rpm, more preferably 1800-2700 rpm, more preferably 2100-2400 rpm; the time is preferably 4-6 h, more preferably 4.5-5.5 h, more preferably 4.8-5.2 h; the vacuum degree is preferably -0.05 to -0.08 MPa, more preferably -0.06 to -0.07 MPa, more preferably -0.063 to -0.066 MPa.
[0050] In the present invention, the high-capacity sodium ion positive electrode slurry preferably comprises the following raw materials: a high-capacity layered oxide positive electrode material, a binder, a conductive agent, carbon nanotubes and a solvent.
[0051] In the present invention, the high capacity layered oxide positive electrode material is preferably O3-Na[Cu 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 ]O2, the binder is preferably polyvinylidene fluoride, the conductive agent is preferably super-p, and the solvent is preferably N-methylpyrrolidone.
[0052] In the present invention, the mass ratio of the high-capacity layered oxide positive electrode material, binder, conductive agent and carbon nanotubes is preferably 94-96:2-3:1.5-2.5:0.1-1, further preferably 94.5-95.5:2.2-2.8:1.6-2.4:0.2-0.8, and more preferably 94.8-95.2:2.4-2.6:1.8-2.2:0.4-0.6.
[0053] In the present invention, the solid content of the high-capacity sodium ion positive electrode slurry is preferably 55-65%, more preferably 56-64%, and more preferably 58-62%.
[0054] In the present invention, the method for preparing the high-capacity sodium ion positive electrode slurry preferably comprises the following steps: mixing various raw materials to obtain the high-capacity sodium ion positive electrode slurry.
[0055] In the present invention, the mixing is preferably vacuum stirring, and the rotation speed of the vacuum stirring is preferably 1500-3000 rpm, more preferably 1800-2700 rpm, and more preferably 2100-2400 rpm; the time is preferably 4-6 h, more preferably 4.5-5.5 h, and more preferably 4.8-5.2 h; the vacuum degree is preferably -0.05 to -0.08 MPa, more preferably -0.06 to -0.07 MPa, and more preferably -0.063 to -0.066 MPa.
[0056] In the present invention, after obtaining the high-voltage sodium ion positive electrode slurry and the high-capacity sodium ion positive electrode slurry, a double-layer coating machine is used to synchronously and continuously complete the coating.
[0057] The present invention also provides the use of the pre-sodiumized positive electrode plate in a sodium ion battery.
[0058] The present invention also provides a sodium ion battery, which comprises the pre-sodiumized positive electrode plate and the hard carbon negative electrode plate.
[0059] The present invention also provides a method for preparing the sodium ion battery, comprising the following steps: combining a pre-sodiumized positive electrode sheet and a hard carbon negative electrode sheet, and sequentially performing rolling, slitting, sheeting, winding, assembling, baking, liquid injection, formation, aging, and capacity division to obtain the sodium ion battery.
[0060] In the present invention, the formation is preferably performed in sequence by a first step of charging, a second step of charging, a third step of charging and a fourth step of discharging.
[0061] In the present invention, the current of the first step charging is preferably 0.15-0.25C, more preferably 0.16-0.24C, more preferably 0.18-0.22C; the target voltage is preferably 3.7-3.9V, more preferably 3.75-3.85V, more preferably 3.78-3.82V.
[0062] In the present invention, the current of the second step charging is preferably 0.35-0.45C, more preferably 0.36-0.44C, more preferably 0.38-0.42C; the target voltage is preferably 3.95-4.05V, more preferably 3.96-4.04V, more preferably 3.98-4.02V.
[0063] In the present invention, the current of the third step charging is preferably 0.15-0.25C, more preferably 0.16-0.24C, more preferably 0.18-0.22C; the target voltage is preferably 4.3-4.4V, more preferably 4.32-4.38V, more preferably 4.34-4.36V.
[0064] In the present invention, the current of the fourth step discharge is preferably 0.15-0.25C, more preferably 0.16-0.24C, more preferably 0.18-0.22C; the target voltage is preferably 3.7-3.9V, more preferably 3.75-3.85V, more preferably 3.78-3.82V.
[0065] In the present invention, the processes not involved are carried out using conventional techniques in the art.
[0066] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0067] Example 1
[0068] The high-capacity layered oxide positive electrode material O3-Na[Cu 1 / 9 Ni 2 / 9 Fe 1 / 3Mn 1 / 3 ]O2, polyvinylidene fluoride, conductive agent-super-p, and carbon nanotubes are added to a stirring tank, and N-methylpyrrolidone is added to control the solid content to 60%. Stir for 5 hours at 2500rpm and -0.05MPa vacuum to obtain a high-capacity sodium ion positive electrode material.
[0069] The high voltage layered oxide positive electrode material P2-Na 2 / 3 [Cu 1 / 3 Mn 2 / 3 ]O2, Na2C2O4, polypyrrole nanofibers and sodium carboxylate are added into a stirring tank, N-methylpyrrolidone is added to control the solid content to 70%, and the mixture is stirred for 5 hours at 2500 rpm and -0.05 MPa vacuum to obtain a high voltage sodium ion positive electrode slurry.
[0070] A double-layer coating machine is used to synchronously and continuously coat the first layer of high-capacity sodium ion positive electrode slurry and the second layer of high-voltage sodium ion positive electrode slurry. The high-voltage sodium ion positive electrode slurry is above the high-capacity sodium ion positive electrode slurry, and the bottom is the current collector. The thickness of the high-voltage sodium ion positive electrode slurry is 13% of the sum of the thickness of the high-voltage sodium ion positive electrode slurry and the high-capacity sodium ion positive electrode slurry, and a pre-sodiumized positive electrode plate is obtained. The schematic diagram of the pre-sodiumized positive electrode plate in this embodiment is as follows: Figure 1 shown.
[0071] The pre-sodiumized positive electrode sheet prepared in this embodiment is matched with a hard carbon negative electrode sheet, and rolling, slitting, sheeting, winding, assembly, baking, liquid injection, formation, aging, and capacity division are completed to obtain a high-performance sodium ion battery of the present invention, wherein the formation process steps are: 0.2C constant current charging to 3.8V, 0.4C constant current charging to 4.0V, 0.2C constant current charging to 4.35V, and 0.2C constant current discharging to 3.8V.
[0072] Comparative Example
[0073] The high capacity layered oxide positive electrode material O3-Na[Cu 1 / 9 Ni 2 / 9Fe 1 / 3 Mn 1 / 3 ]O2, positive electrode sodium compensation material Na2C2O4, binder-polyvinylidene fluoride, conductive agent-super-p, and carbon nanotubes are added to a stirring tank, and N-methylpyrrolidone is added to control the solid content to 60%. Stir for 5 hours at 2500rpm and -0.05MPa vacuum to obtain a high-capacity sodium ion positive electrode material.
[0074] An extrusion coater is used to synchronously and continuously complete the coating of high-capacity sodium-ion positive electrode slurry.
[0075] The positive electrode slurry prepared in this comparative example is matched with a hard carbon negative electrode sheet, and rolling, slitting, sheeting, winding, assembly, baking, liquid injection, formation, aging, and capacity division are completed to obtain a high-capacity sodium ion battery, wherein the formation process steps are: 0.2C constant current charging to 3.8V, 0.4C constant current charging to 4.0V, 0.2C constant current charging to 4.35V, and 0.2C constant current discharging to 3.8V.
[0076] The sodium ion batteries of Example 1 and Comparative Example were subjected to performance tests:
[0077] (1) Calculation of the first coulombic efficiency: Extract the charge and discharge capacity of the formation and capacity of a single sodium-ion battery and calculate the first coulombic efficiency - ICE of the sodium-ion battery. The test results are as follows: Figure 2 As shown. Figure 2 It can be seen that the first coulombic efficiency of the high-performance sodium ion battery of the present invention is 95.05%, while the first coulombic efficiency of the sodium ion battery of the comparative example is 92%, which shows that the pre-sodiumization technology of the present invention has achieved a very good effect. This is due to the better interface dynamics of the present invention than the comparative example, which enables the positive electrode sodium compensation material to completely remove the excess sodium ions, and the polarization is small and the reaction is rapid, so that the sodium loss of the negative electrode can be compensated, thereby improving the first coulombic efficiency of the sodium ion battery.
[0078] (2) Cyclic performance test: Under normal temperature conditions, the battery is charged to 4.0V at a rate of 1C, the cut-off current of constant voltage charging is 0.05C, and the battery is discharged to 2V at a rate of 1C. The test results are as follows: Figure 3 As shown. Figure 3 It can be seen that the cycle life of the high-performance sodium ion battery of the present invention is relatively excellent. After 1398 cycles, the capacity retention rate is 97.7%, while the capacity retention rate of the comparative example is 92.4% after 1411 cycles. The high-performance sodium ion battery of the present invention has a good cycle life, which is due to the good use of the positive electrode pre-sodium technology of the present invention.
[0079] (3) Low temperature performance test: At -40°C, charge to 4.0V at a rate of 0.5C, with a cut-off current of 0.05C for constant voltage charging, and record the charge capacity at this time; discharge to 2V at a rate of 1C, and record the discharge capacity at this time. Compare the above charge and discharge capacities with the charge and discharge capacities at room temperature, and calculate the charge and discharge capacity retention rate of the battery at low temperature; the test results are as follows: Figure 4 As shown. Figure 4 It can be seen that the high-performance sodium ion battery of the present invention has obvious low-temperature performance advantages over the comparative example battery, and both the low-temperature charging capacity and the low-temperature discharging capacity are relatively excellent. This is also due to the pre-sodiumization technology of the present invention, which reduces the internal impedance of the battery, improves the interface stability and kinetic characteristics, and reduces polarization, so that the high-performance sodium ion battery of the present invention has excellent low-temperature performance.
[0080] (4) DCR test: Test the DCR of sodium-ion batteries at different SOCs, temperature: 25°C, discharge rate: 4C, discharge time: 10s; the test results are as follows Figure 5 As shown, from Figure 5 It can be seen that the DCR of the high-performance sodium ion battery of the present invention is much lower than that of the comparative example battery, which is consistent with the above cycle performance and low-temperature performance, verifying that the pre-sodiumization technology and high-performance sodium ion battery of the present invention have reliable performance advantages.
[0081] (5) Rate discharge test: The sodium ion battery of Example 1 was charged to 4.0 V at a constant current of 2C and discharged to 2 V at a rate of 30C; the sodium ion battery was charged to 4.0 V at a constant current of 2C and discharged to 2 V at a rate of 1C. The rate discharge capability was compared. The test results are as follows: Figure 6 As shown, from Figure 6 It can be seen that the high-performance sodium ion battery of the present invention has the ability to discharge continuously at a rate of 30C, which once again verifies the reliability and application prospects of the pre-sodiumization technology and high-performance sodium ion battery technology of the present invention.
[0082] Example 2
[0083] The high-capacity layered oxide positive electrode material O3-Na[Cu 1 / 9 Ni 2 / 9 Fe 1 / 3Mn 1 / 3 ]O2, polyvinylidene fluoride, conductive agent-super-p, and carbon nanotubes are added to a stirring tank, and N-methylpyrrolidone is added to control the solid content to 62%. Stir for 4 hours at 1800rpm and -0.08MPa vacuum to obtain a high-capacity sodium ion positive electrode material.
[0084] The high voltage layered oxide positive electrode material P2-Na 2 / 3 [Cu 1 / 3Mn 2 / 3 ]O2, Na2C2O4, polypyrrole nanofibers and sodium dodecyl sulfate were added to a stirring tank, and N-methylpyrrolidone was added to control the solid content to 73%. The mixture was stirred at 2800 rpm and a vacuum degree of -0.06 MPa for 4.5 h to obtain a high-voltage sodium ion positive electrode slurry.
[0085] A double-layer coating machine is used to synchronously and continuously coat the first layer of high-capacity sodium ion positive electrode slurry and the second layer of high-voltage sodium ion positive electrode slurry. The high-voltage sodium ion positive electrode slurry is above the high-capacity sodium ion positive electrode slurry, and the bottom is the current collector. The thickness of the high-voltage sodium ion positive electrode slurry is 11% of the sum of the thickness of the high-voltage sodium ion positive electrode slurry and the high-capacity sodium ion positive electrode slurry, and a pre-sodium positive electrode sheet is obtained. The pre-sodium positive electrode sheet prepared in this embodiment is matched with a hard carbon negative electrode sheet, and rolling, slitting, sheeting, winding, assembly, baking, injection, formation, aging, and capacity division are completed to obtain a high-performance sodium ion battery of the present invention, wherein the formation process steps are: 0.18C constant current charging to 3.7V, 0.35C constant current charging to 3.95V, 0.23C constant current charging to 4.4V, and 0.15C constant current discharge to 3.75V.
[0086] The performance test was carried out according to the method of Example 1, and the test results were as follows: the first coulombic efficiency was 94.96%; after 1425 cycles, the capacity retention rate was 97.3%; the charge retention rate was 95.52% at -40°C, and the discharge retention rate was 98.17%; the energy density was 156Wh / kg.
[0087] Example 3
[0088] The high-capacity layered oxide positive electrode material O3-Na[Cu 1 / 9 Ni 2 / 9Fe 1 / 3 Mn 1 / 3]O2, polyvinylidene fluoride, conductive agent-super-p, and carbon nanotubes are added to a stirring tank, and N-methylpyrrolidone is added to control the solid content to 55%. Stir for 6 hours at 2800rpm and -0.05MPa vacuum to obtain a high-capacity sodium ion positive electrode material.
[0089] The high voltage layered oxide positive electrode material P2-Na 2 / 3 [Cu 1 / 3 Mn 2 / 3 ]O2, Na2C2O4, polypyrrole nanofibers and sodium olefin sulfonate are added to a stirring tank, N-methylpyrrolidone is added to control the solid content to 65%, and stirring is carried out at 1500rpm and -0.07MPa vacuum for 5h to obtain a high-voltage sodium ion positive electrode slurry.
[0090] A double-layer coating machine is used to synchronously and continuously coat the first layer of high-capacity sodium ion positive electrode slurry and the second layer of high-voltage sodium ion positive electrode slurry. The high-voltage sodium ion positive electrode slurry is above the high-capacity sodium ion positive electrode slurry, and the bottom is the current collector. The thickness of the high-voltage sodium ion positive electrode slurry is 15% of the sum of the thickness of the high-voltage sodium ion positive electrode slurry and the high-capacity sodium ion positive electrode slurry, and a pre-sodium positive electrode sheet is obtained. The pre-sodium positive electrode sheet prepared in this embodiment is matched with a hard carbon negative electrode sheet, and rolling, slitting, sheeting, winding, assembly, baking, injection, formation, aging, and capacity division are completed to obtain a high-performance sodium ion battery of the present invention, wherein the formation process steps are: 0.23C constant current charging to 3.9V, 0.45C constant current charging to 4.05V, 0.15C constant current charging to 4.35V, and 0.2C constant current discharge to 3.9V.
[0091] The performance test was carried out according to the method of Example 1, and the test results were as follows: the first coulombic efficiency was 95.12%; after 1452 cycles, the capacity retention rate was 97.5%; the charge retention rate was 95.46% at -40°C, and the discharge retention rate was 98.02%; the energy density was 152Wh / kg.
[0092] As can be seen from the above embodiments, the present invention provides a pre-sodiumized positive electrode sheet, comprising a high-voltage sodium ion positive electrode slurry, a high-capacity sodium ion positive electrode slurry and a current collector; the thickness of the high-voltage sodium ion positive electrode slurry is 10-15% of the sum of the thickness of the high-voltage sodium ion positive electrode slurry and the high-capacity sodium ion positive electrode slurry. In the present invention, due to the effective use of the positive electrode sodium supplementation technology, the irreversible sodium loss of the hard carbon negative electrode is reduced, the kinetic performance of the sodium ion battery is improved, and the polarization is reduced, so that the high-performance sodium ion battery has a first coulomb efficiency of more than 95%, an energy density of more than 150Wh / kg, a cycle life of more than 6000 weeks, the ability to charge and discharge at -40°C, and the ability to continuously discharge at a rate of 30C, thereby improving the comprehensive electrochemical performance of the sodium ion battery.
[0093] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A pre-sodiumized positive electrode plate, characterized in that: From top to bottom, they are high voltage sodium ion positive electrode slurry, high capacity sodium ion positive electrode slurry and current collector; The thickness of the high-voltage sodium ion positive electrode slurry is 10-15% of the sum of the thickness of the high-voltage sodium ion positive electrode slurry and the high-capacity sodium ion positive electrode slurry; The high-capacity sodium ion positive electrode slurry is made of the following raw materials: a high-capacity layered oxide positive electrode material, a binder, a conductive agent, carbon nanotubes and a solvent; The high capacity layered oxide positive electrode material is O3-Na[Cu 1 / 9 Ni 2 / 9 Fe 1 / 3 Mn 1 / 3 ]O2, the binder is polyvinylidene fluoride, the conductive agent is super-p, and the solvent is N-methylpyrrolidone; The mass ratio of the high-capacity layered oxide positive electrode material, the binder, the conductive agent and the carbon nanotubes is 94-96: 2-3: 1.5-2.5: 0.1-1; The high voltage sodium ion positive electrode slurry is made of the following raw materials: high voltage layered oxide positive electrode material, positive electrode sodium compensation material, conductive polymer, dispersant and solvent; The high voltage layered oxide positive electrode material is P2-Na 2 / 3 [Cu 1 / 3 Mn 2 / 3 ]O2, the positive electrode sodium compensation material is Na2C2O4 or Na2MnO3, the conductive polymer is polypyrrole nanofiber, the dispersant is sulfonate, sulfate ester salt, carboxylate or oleate; the solvent is N-methylpyrrolidone; The mass ratio of the high voltage layered oxide positive electrode material, the positive electrode sodium compensation material, the conductive polymer and the dispersant is 95-97: 1.5-2.5: 1-2: 0.1-1; The solid content of the high voltage sodium ion positive electrode slurry is 65-75%; The solid content of the high-capacity sodium ion positive electrode slurry is 55-65%.
2. The pre-sodiumized positive electrode sheet according to claim 1, characterized in that: The method for preparing the high-voltage sodium ion positive electrode slurry comprises the following steps: mixing various raw materials to obtain the high-voltage sodium ion positive electrode slurry; The mixing is vacuum stirring, the rotation speed of the vacuum stirring is 1500 to 3000 rpm, the time is 4 to 6 hours, and the vacuum degree is -0.05 to -0.08 MPa.
3. The pre-sodiumized positive electrode sheet according to claim 2, characterized in that: The method for preparing the high-capacity sodium ion positive electrode slurry comprises the following steps: mixing various raw materials to obtain the high-capacity sodium ion positive electrode slurry; The mixing is vacuum stirring, the rotation speed of the vacuum stirring is 1500 to 3000 rpm, the time is 4 to 6 hours, and the vacuum degree is -0.05 to -0.08 MPa.
4. Use of the pre-sodiumized positive electrode sheet according to any one of claims 1 to 3 in a sodium ion battery.
5. A sodium ion battery, characterized in that: The sodium ion battery comprises the pre-sodiumized positive electrode sheet and the hard carbon negative electrode sheet as described in any one of claims 1 to 3.
6. The method for preparing a sodium ion battery according to claim 5, characterized in that: The method comprises the following steps: combining a pre-sodiumized positive electrode sheet and a hard carbon negative electrode sheet, and sequentially rolling, slitting, sheeting, winding, assembling, baking, liquid injection, formation, aging, and capacity division to obtain the sodium ion battery; The step of charging, discharging, and discharging are performed sequentially in the first step, the second step, the third step, and the fourth step. The current of the first step charging is 0.15-0.25C, and the target voltage is 3.7-3.9V; The current of the second step charging is 0.35-0.45C, and the target voltage is 3.95-4.05V; The current of the third step charging is 0.15-0.25C, and the target voltage is 4.3-4.4V; The current of the fourth step discharge is 0.15-0.25C, and the target voltage is 3.7-3.9V.
